COMMUNICATION OF LOCAL WISDOM ON RAIN PROTECTION THROUGH PLANT MEDIA IN BARABAI - Mardiana; Hayat, Muzahid Akbar; Ayuni, Risa Dwi (Moestopo International Review on Social, Humanities, and Sciences, 2024)
The purpose of this study is to analyze the motives for using chili peppers and taro leaves as a rain-deterring plant medium, the process and patterns of communication and how to preserve the tradition as local wisdom communication in the Kahakan Village community, Barabai. The type of research used is a qualitative research method with a phenomenological study approach. Data collection techniques use observation, interview and documentation methods. The results showed that the motive for using chili peppers and taro leaves as a medium for rain warding plants is a tradition of previous parents who are considered as intermediaries and not against religion. The communication process of rain deterrence rituals in the form of symbols in the form of chilies and taro leaves which are interpreted according to the nature of the two plants, namely spicy or hot and waterproof, the ritual process is accompanied by reading basmallah, shalawat and prayer. Communication patterns use symbols of chili peppers and taro leaves where the meaning is generally understood by the local community. The way to preserve this tradition is by introducing it to their children’s generation through stories and inviting them persuasively to participate in the rain deterrence ritual when there is a celebration in the community.